A NEW HIGH-RESOLUTION CHITINOZOAN COMPOSITE STANDARD FOR THE EAST BALTIC LOWER SILURIAN SUCCESSION BASED ON NUMERICAL ANALYSIS - Rubel M.; Ainsaar L.; Nestor V.; Männik P.; Nõlvak J.; Harris M.T.; Sheehan P.M. (My University, 2006)
The chitinozoan successions (zonation) in the Llandovery and Wenlock deposits, accumulated along the northern shelf edge of the Livonian Basin, an embayment of the Palaeobaltic sea, is studied and used for time-rock correlation of the area. Analysis of the ranges of 180 taxa from 44 sections (41 of them well-sections) by graphic correlation revealed largely compatible successions of taxa as well as local stratigraphic gaps in both shelf and basin sections. Alternatives to graphic methods also produced composite standards based on stratigraphic relationships (below, co-occurring, or above) of taxonomic ranges and considered as palaeontological time scales (composites) similar to zonal schemes. We constructed such a scale using the DISTR algorithm to analyse the distribution of 84 taxa and recognized 41 datum planes. This scale includes the traditional regional and global chitinozoan zones and the associated chronological standards (including regional stages). The BioGraph and DISTR algorithms were used to study diversity changes, and to illustrate patterns of originations and extinctions of the chitinozoans. Correlation plots between composite standard and particular sections reveal variations in sedimentary rock accumulation patterns, supporting the results of sequence stratigraphic analysis of the study interval.
Keywords: CHITINOZOAN TIMESCALES; LLANDOVERY; PALAEOBALTIC BASIN; WENLOCK; Paleozoic::Silurian::Llandovery; Палеозой::Силурийская::Лландоверийский